Türkiye’s Contemporary Energy Diplomacy: Regional Directions and Strategic Partnerships (Халықаралық қатынастар және халықаралық құқық сериясы, 2025)
In the context of the growing demand for energy resources and the transformation of the global energy system, energy diplomacy has become an increasingly important instrument of states’ foreign policy. This study examines the main features of Türkiye’s energy diplomacy in the contemporary international conditions. The main objective of the research is to analyze the structure of Türkiye’s energy sector and the key directions of its energy cooperation with regions worldwide. The results of the study demonstrate that Türkiye’s energy policy is shaped by its heavy reliance on energy imports, the steady growth in domestic energy demand, and the need to diversify energy sources. In this context, Türkiye’s geographical position plays a crucial role. In other words, the geographical aspect enables the country to serve as a transit hub between resource-rich regions (Russia, the Middle East, North Africa, Central Asia, and the Caucasus) and European energy markets. At the same time, it facilitates the development of multi-vector cooperation with the United States of America and China. These findings led us to a better understanding of the main directions and regional dimensions of Türkiye’s contemporary energy diplomacy. They also highlight the growing importance of regional energy cooperation in shaping the country’s foreign policy priorities.Keywords: Türkiye, Energy Diplomacy, Energy Cooperation, Transit Hub, Multi-Vector Cooperation.